(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Study was conducted to evaluate the effect of (Myrtus communis) oil on the weight of body and some Hematological in the local male rabbits. (15) rabbits average (1078-1088 ) gram were divided to (3) groups, every group (5) rabbits, group (1) the control gives only (0.2) ml tap water orally, while group (2), (3) gives Myrtle oil (0.1) ml/kg,(0.2) ml/kg respectively orally for (2) month. We conducted that the administration of Myrtle oil produces a significance decrease (P˂0.01) at 0.1ml/Kg.B.W. and 0.2ml/Kg.B.W in the body weight, there is a significance increase (P˂ 0.05) at 0.1ml/Kg.B.W. in values of RBCs, WBCs, Hb and PCV, there is a significance decrease (P<0.05) at 0.2ml/Kg.B.W. in values of RBCs,WBCs, Hb and PCV. While there is no significance) P˂ 0.05) in the value of PLT. We concluded that, the administration of Myrtle oil in low dose produces good effects whereas administration of it in high dose produce bad effects in the body functions.